2016
DOI: 10.1016/j.scitotenv.2016.02.092
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessments of heavy metal exposure via consumption of marine mussels collected from anthropogenic sites

Abstract: A total of 40 marine mussel Perna viridis populations collected (2002-2009) from 20 geographical sites located in two busy shipping lanes namely the Straits of Malacca (10 sites; 16 populations) and the Straits of Johore (8 sites; 21 populations) and three populations (2 sites) on the east coast of Peninsular Malaysia, was determined for Cd, Cu, Fe, Ni, Pb and Zn concentrations. In comparison with the maximum permissible limits (MPLs) set by existing food safety guidelines, all metal concentrations found in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
4
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 28 publications
4
51
4
14
Order By: Relevance
“…(Figure 2 c and d). Yap et al (2016) (2007) report average Cd concentration of 1.3 ug/g (dw) in mussel (Semimytilus algosus) from White Island of Peru, being lower values than found at Atico and Marcona of this study, possibly because at White Island there were no anthropogenic sources nearby.…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…(Figure 2 c and d). Yap et al (2016) (2007) report average Cd concentration of 1.3 ug/g (dw) in mussel (Semimytilus algosus) from White Island of Peru, being lower values than found at Atico and Marcona of this study, possibly because at White Island there were no anthropogenic sources nearby.…”
Section: Resultscontrasting
confidence: 56%
“…Aulocomya ater with 0.31 and 0.36 ug Pb/g (dw) and Mytilus edulis with 0.21 and 0.42 ug Pb /g (dw) at Punta Maqueda and Arroyo La Mata respectively (Perez et al, 2005). At Chetumal Quintana Roo bahia, Mexico, mussel (Mytilopsis sallei Récluz, 1849) were evaluated, finding Pb in the range of 0.31 to 3.23 ug/g (dw) (Diaz et al, 2006); in the same way Yap et al, (2016) found on Perna viridis at peninsular coast of Malaysia, 0.27 to 10.4 ug Pb/g (wwt). Cadmium.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It should be considered that elements in a marine environment have a more complex distribution than organic pollutants and reflect more faithfully local anthropogenic inputs, natural sources, and hydrological conditions [31]. Therefore, one of the most important of these variables is the geographical origin of the said mussels, which in turn is related to the water quality of these regions [32,33,34,35,36,37,38]. However, according to food consumption surveys, geographic origin is not the most important criterion that guides the purchase of mussels by Spanish consumers, but their type of conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we use the PTWI for organic Hg (1.6 g or 0.0016 mg) per kg body weight per week. The bodyweight category is 60 kg for adults (Ullah, Maksud, Khan, Lutfa, & Quraishi, 2017;Yap, Cheng, Karami, & Ismail, 2016). The PTWI based on body weight category or Maximum Weekly Intake (MWI) was calculated using the formula:…”
Section: Data Analysis and Health Risk Assessmentmentioning
confidence: 99%